2015
DOI: 10.3892/ijo.2015.2987
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane reduces molecular response to hypoxia in ovarian tumor cells independently of their resistance to chemotherapy

Abstract: One of the recently emerging anticancer strategies is the use of natural dietary compounds, such as sulforaphane, a cancer-chemopreventive isothiocyanate found in broccoli. Based on the growing evidence, sulforaphane acts through molecular mechanisms that interfere with multiple oncogenic pathways in diverse tumor cell types. Herein, we investigated the anticancer effects of bioavailable concentrations of sulforaphane in ovarian carcinoma cell line A2780 and its two derivatives, adriamycin-resistant A2780/ADR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…SFN has a safe cytotoxicity profile towards the normal cells thus it can be utilized in the development of safe cancer treatment strategies (Hussain et al 2013 ; Kallifatidis et al 2011 ). In addition, sulforaphane can overcome the chemoresistance of cancer cells (Lan et al 2015 ; Pastorek et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…SFN has a safe cytotoxicity profile towards the normal cells thus it can be utilized in the development of safe cancer treatment strategies (Hussain et al 2013 ; Kallifatidis et al 2011 ). In addition, sulforaphane can overcome the chemoresistance of cancer cells (Lan et al 2015 ; Pastorek et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Withaferin A, a steroidal lactone, synergizes with doxorubicin against OvCa, which is brought about mainly by autophagy mediated by reactive oxygen species [ 86 ]. Withaferin-A, Amla extracts, ellagic acid, and resveratrol have been reported to prevent cisplatin resistance, while sulforaphane overcomes doxorubicin and cisplatin resistance in OvCa [ 87 90 ]. Curcumin, epigallocatechin 3-gallate, resveratrol, lycopene, sulforaphane, and Withaferin-A modulate pathways deregulated in cancer stem cells such as Wnt/β-catenin, Sonic hedgehog, and Notch, mainly interfering with the self-renewal of cancer stem cells [ 84 , 91 ].…”
Section: Chemopreventive Agents For Ovarian Cancermentioning
confidence: 99%
“…Samples: cont-control, G GYY4137(10 lM), D DMOG (100 lM), and hyp 2 % hypoxia responses (p53, ARE, IRF1, Pax6, and XRE) and suppressing responses supporting tumor progression (AP1 and HIF-1). Further we have shown that sulforaphane decreases the level of HIF-1a protein without affecting its transcription and stability [25]. In this work, we focused on the role of H 2 S in ovarian tumor cells A2780.…”
Section: Discussionmentioning
confidence: 99%